A numerical investigation on the heat transfer and turbulence production characteristics induced by a swirl spacer in a single-tube geometry under single-phase flow condition. (1st September 2021) - Abe, Satoshi; Okagaki, Yuria; Satou, Akira; Sibamoto, Yasuteru
Highlights: The heat transfer characteristics in a single tube with the simulant swirl spacer was investigated through isotropic RANS simulation. The predicted secondary flow intensity ( SFI ) and turbulence intensity ( TI ) with the SST k – ω model was similar to the correlations proposed by Xiong et al. (2020). The predicted inner surface temperature and HTC values with the SST k – ω model relatively agreed with the experimental data. The CFD investigation implied that the direct effect on the turbulence production induced by the swirl spacer is confined at z/D < 10, resulting in the heat transfer augmentation. Abstract: Heat transfer in the rod bundle is augmented by the mixing vanes on the spacer grid. We conducted a computational fluid dynamics (CFD) simulation with three isotropic turbulence models – standard k–ε, realizable k– ε, and SST k–ω models – to investigate the relationship between heat transfer and turbulence behaviors downstream a simulant spacer (with four vanes) in a single tube under single-phase flow conditions. Quantitatively, the predicted heat transfer coefficient (HTC), secondary flow intensity, and turbulence intensity with the SST k–ω model displayed a better agreement (than the other isotropic models) with the experimental data in previous studies. Moreover, the turbulence production was localized in the near-spacer region (z/D < 10, where D is the inner diameter), which corresponds with the HTC augmentation region. These results indicate that examining the turbulence production when discussing the HTC augmentation downstream the spacer is essential.